Geographic distribution and temporal trends of malnutrition and anaemia among women and children in malaria-endemic districts of India: a comparative analysis of NFHS-4 and NFHS-5 - J., Harshitha; M., Avinash; M., Shrinivasa B.; Tiwary, Juhi; M., Sanjana; L., Pavan B.; Bankoti, Kajal; Negi, Gunjan; Tomer, Viprasha; Chalageri, Vani H. (International Journal Of Community Medicine And Public Health, 2026)
Introduction: In India malaria and malnutrition are major public health concerns. However, this interplay between anaemia and malnutrition remain poorly understood at the administrative unit (district) level. This study aims to analyse changes in the geographical distribution and temporal trends of malnutrition, and anaemia among children and women in the malaria endemic districts with Annual Parasite Index > 1. Methods: This study used district-level data from National Family Health Survey –4 (NFHS-4) (2015–16) and National Family Health Survey-5 (NFHS-5) (2019–21) to assess geographical distribution and temporal patterns of malnutrition and anaemia in 29 malaria-endemic districts of India with API≥1 (2024). District-level trends across survey were compared and mapped using R software. Results: Between NFHS-4 and NFHS-5, several malaria-endemic districts (API≥1) demonstrated meaningful improvements in child nutrition and anaemia indicators. Stunting declined notably in Uttar Bastar Kanker (36.3% to 24.8%) and Godda (54.0% to 39.4%). Wasting showed reduction in Bastar (33.9% to 20.4%), while underweight decreased in Kabeerdham (38.4% to 27.3%). Encouraging improvements in anaemia were observed among children in South Garo Hills (74.9% to 33.6%) and among pregnant women in Uttar Bastar Kanker (56.7% to 33.4%). Conclusion: The observed reductions in malnutrition and anaemia across multiple malaria-endemic districts highlight the potential impact of focused nutrition and maternal health interventions. Strengthening and scaling successful district-level strategies can support integrated approaches toward improving nutritional outcomes and advancing malaria elimination goals by 2030.